Model Tata Kelola Komputasi Hijau Berbasis Dokumen untuk Universitas Bina Nusantara - Putri, Nuril Kusumawardhani Soeprapto; Argogalih, Argogalih; Hudiarto, Hudiarto (Bina Nusantara University, 2013)
The lack of green computing governance model for environment of universities in Indonesia becomes one major factor to conduct this research. In fact, the teaching and learning activities in campuses depend on support of information system and information technology. Various studies on green computing were observed. However, the suitable model for green computing in the area of private university Indonesia has not been observed yet. Referring to Green ICT Framework by University of Michigan and Connection Research as well as green computing framework by Adcuent, the green computing model for private university in Indonesia was developed through this research. Although the research object was observed in Bina Nusantara University, Jakarta, Indonesia, it is adoptable for other private universities to evaluate their information system and information technology performance surround campuses. Green computing governance is part of information system and information technology strategic plan. Therefore, the management of university should fully concern towards this matter.